From sad, stray and abandoned to healthy and cheerful cats / Melati Desa - Desa, Melati (Academy of Language Studies, 2021)
Even though Malaysians are known as kind and loving citizens, we can see so many stray and abandoned cats around us. There are even a few extreme cases, such as stray cats being killed or thrown from high places with the intention of killing them. These are signs of animal abuse which is on the rise in Malaysia. Is feeding stray cats good? Please don’t feed stray cats. Yes, you think you are helping the cats to survive, but feeding stray cats can actually hurt them. There are many diseased and malnourished stray cats as a result of people leaving out food for them. This is because the presence of food causes a clowder of cats to get together. They fight over territo¬ries and spread diseases among each other. At the same time, they breed and suddenly, the number of cats increases in one small area and their population will eventually grow too large for you to feed them. Soon, due to overpopulation which leads to territorial disputes, the weaker ones will starve or get injured that can lead to deaths